(untitled) (Ágora UNLaR, 2021)
En esta entrevista a la escritora, periodista e investigadora argentina Irene Chikiar Bauer, hablamos de temas tales como el arte de la escritura de biografías y los límites, muchas veces difusos, entre el rol de la escritora y la del artista. Recorremos, además, las investigaciones y publicaciones de la autora, con un especial foco en sus producciones sobre figuras femeninas de los siglos XIX y XX. Finalmente, entrecruzamos, desde el encuentro, los roles de la autora en sus actividades como escritora, periodista, docente e investigadora. On the art of biography. An interview with Irene Chikiar Bauer Abstract In this interview with the Argentine writer, journalist and researcher Irene Chikiar Bauer, we talk about topics such as the art of writing biographies and the blurring boundaries between the role of the writer and that of the artist. We also go through the author’s research studies and publications, with a special focus on her productions on female figures from the 19th and 20th centuries. Finally, from a common ground, we intersect the roles of the author in her activities as a writer, journalist and teacher-researcher. Keywords: biography, Eduarda Mansilla, Virginia Woolf, Victoria Ocampo, Chikiar Bauer